Dyes Removal from Aqueous Solution using Chemical Treated Empty Fruit Bunch at Various pH - Saiful Azhar, Saad (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.